Evaluating the membrane fouling control ability of a reciprocation membrane bioreactor (rMBR) system - P.T. Nguyen; B.T. Dang; Q.T. Huynh; X.D. Nguyen; H.H. Nguyen; K.J. Lee; X.T. Bui (Vietnam Journal of Science, Technology and Engineering, 2022)
Membrane bioreactors (MBRs) are being increasingly applied to many full-scale plants around the world to treat both municipal and industrial wastewater. However, membrane fouling and energy consumption are significant challenges to broader applications of MBRs. By using a new MBR configuration, this research aims to compare the performance between a conventional MBR and a reciprocation MBR (rMBR) that uses inertial forces without air scouring for fouling reduction. The results show that there was no difference in chemical oxygen demand (COD) (92-98%) or total nitrogen (TN) (71-77%) after 280 d of operation under the same influent constraints. However, by using the inertial force, the fouling rates were 0.35 mbar/d for the rMBR, resulting in a significantly lower fouling rate in comparison with a conventional MBR and other literature reports. Thus, the lower energy consumption over long-term operation of a rMBR could be a promising solution to overcome the drawbacks of a MBR.